Applied Entomology and Zoology - Applied Entomology and Zoology (Springer Nature, 2026)
Applied Entomology and Zoology publishes articles concerned with applied entomology, applied zoology, agricultural chemicals, and pest control in English. Contributions of a basic and fundamental nature may be accepted at the discretion of the Editor. The journal particularly welcomes submissions in the following entomological and zoological areas: taxonomy, morphology, phylogeny, ecology, behavior, physiology, evolution, genomics, metabolomics, molecular biology, bioactive compounds, bioresources and functional utilization, and new methods and techniques.
FI 0.52
Q2
Keywords: Life Sciences; Entomology; Ciencias de la vida; Entomología; Zoología; Acuerdos transformativos; Transformative agreements; Entomología aplicada; Zoología aplicada; Agroquímicos